Penggunaan Media Audiovisual Dalam Pengajaran Katekase - Elisabeth Yecilda Woga; Emmeria Tarihoran (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Catechesis is the Church’s effort to spread God’s saving work to humanity in everyday life, with the aim of guiding and instilling Christian values. The challenge faced in the current technological era is how to attract the attention of the people in the catechesis teaching process considering that traditional methods such as lectures tend to be boring. This research uses a qualitatie descriptive method through literature study to understand the application of audiovisual media in the context of catechesis participantas, facilitate their understanding of the material being taught and increase their anthsiasm fot learning. Even though thereare several obstacles such as a lack of facilities and the catechist’understanding oftemedia,the use of audiovisual media has great potential to increase the effectiveness of catechesis learning.